Laboratory Conﬁrmation Human Specimens Suspected of Anthrax in Kulonprogo District of Yogyakarta Special Region - Khariri, Khariri; Muna, Fauzul; Rukminiati , Yuni (KnE Social Sciences, 2019)
Anthrax is an acute zoonoses infectious disease caused by Bacillus anthracis bacteria. Bacillus anthracis had ability to form endospores for self-defense. Anthrax infectioncouldbedividedintofourtypesnamelyskinanthrax,gastrointestinalanthrax, anthrax of the respiratory tract (lung) and meningitis anthrax. The examination was performed to conﬁrm the diagnosis of patients suspected of being infected with Bacillus anthracis. The examination methods consisted of culture for whole blood spesimens, konvensional polymerase chain reaction (PCR) on growing colonies and whole blood specimens without growing colony, and enzyme-linked immunosorbent assay (ELISA) for blood serum spesimens. The 6 cultured specimens, there were 2 colony-growing specimens with 1 identical colony with Bacillus anthracis colonies. The colonies conﬁrmed with PCR and only 1 positive as Bacillus anthracis pathogens. The 6 specimens examined there was a positive specimen of Bacillus anthracis pathogen. Keywords: anthrax, laboratory examination, Yogyakarta Special Region